Morphine decreases ticagrelor concentrations but not its antiplatelet effects: a randomized trial in healthy volunteers. (23rd November 2015) - Hobl, Eva‐Luise; Reiter, Birgit; Schoergenhofer, Christian; Schwameis, Michael; Derhaschnig, Ulla; Kubica, Jacek; Stimpfl, Thomas; Jilma, Bernd
Abstract: Background: Our recent drug interaction trial with clopidogrel shows that morphine decreases the concentrations and pharmacodynamic effects of clopidogrel, which could lead to treatment failure in susceptible individuals. We hypothesized that the pharmacodynamic consequences of drug–drug interactions would be less between morphine and ticagrelor. Materials and methods: Twenty‐four healthy subjects received a loading dose of 180 mg ticagrelor together with placebo or 5 mg morphine intravenously in a randomized, double‐blind, placebo‐controlled, crossover trial. Pharmacokinetics were determined by liquid chromatography tandem mass spectrometry, and ticagrelor pharmacodynamic effects were measured by platelet function tests (whole blood platelet aggregation: multiplate, platelet plug formation: PFA‐100, vasodilator‐stimulated phosphoprotein (VASP) phosphorylation assay). Results: Concomitant i.v. injection of morphine slows drug resorption of ticagrelor and its active metabolite ( P < 0·05) by 1 h and decreases plasma levels of ticagrelor and its active metabolite by 25–31% ( P ≤ 0·03) and the drug exposure (area under the curve) by 22–23% ( P ≤ 0·01). Importantly, however, the pharmacodynamic effects of ticagrelor on platelet aggregation in whole blood, platelet plug formation and VASP phosphorylation are not affected by morphine. Conclusions: Morphine co‐administration moderately decreases ticagrelor plasma concentrations but does not inhibit its pharmacodynamic effects in healthy volunteers within 6 h after drug administration. Limitations of our trial include the investigation in healthy volunteers under standardized conditions, which does not necessarily reflect a realistic emergency scenario.